(untitled) - Patterson, James; 1947-; Roughan, Howard (New York, NY, 2022)
Imagine everyone's surprise when Carter von Oehson, a sophomore in Dr. Dylan Reinhart's Abnormal Psychology class, posts on Instagram that he plans to kill himself. Twenty-four hours later and still no one has seen him. The one person convinced he's still alive is his father, Mathias von Oehson. But what Mathias knows and how he knows it would ultimately reveal a secret so damaging that it would be as if he were committing suicide himself. Dylan now finds himself wrapped up in multi-million-dollar secrets and danger and it's going to take every bit of his wit to stay ahead of his enemy. Print run 45,000.
Keywords: Fiction; Chief executive officers; Fiction; Rich people; Fiction; Fathers and sons; Suicide victims; Secrecy; Fiction; Fiction; Art thefts; Fiction; Fiction; College teachers; Investigation; New York (State); Women detectives; Fiction; Fiction; Police; Fiction; New York (State); Missing persons; New York (State); New York (N.Y.); Fiction; Detective and mystery fiction; Thrillers (Fiction)